Development of a cross-contamination-free hydrogen sampling methodology and analysis of contaminants for hydrogen refueling stations. (1st October 2022) - Janßen, Holger; Kroener, Michael; Dyck, Alexander; Vehse, Martin; Wark, Michael; Agert, Carsten
Abstract: Hydrogen used in proton exchange membrane-based fuel cell applications is subject to very high quality requirements. While the influences of contaminations in hydrogen on long-term stability have been intensively studied, the purity of hydrogen for mobile applications provided at hydrogen refueling stations (HRS) is rarely analyzed. Hence, in this study, we present sampling of hydrogen at HRS with a specially designed mobile tank for up to 70 MPa. These samples are precisely analyzed with a sophisticated ion molecule reaction mass spectrometer (IMR-MS), able to determine concentrations of contaminants down to the ppb-level. Sampling and analysis of hydrogen at an HRS supplied by electrolysis revealed a high purity, but likewise considerable contaminations above the threshold of the international standard ISO 14687:2019. In this study, a state-of-the-art analysis coupled with a developed methodology for fuel cell electric vehicle-independent sampling of hydrogen with a mobile tank system is demonstrated and applied for comprehensive studies of hydrogen purity. Highlights: Development of a methodology for the contamination-free sampling of hydrogen. Application of ion molecule reaction mass spectrometry for H2 quality analysis. Analysis of contaminants in hydrogen referring to ISO 14687/EN 17124. Study of a hydrogen refueling station with a mobile tank revealed high quality of H2 . Higher concentrations of H2 O, N2, CO2 and CO were identified as particularly critical.